ANALISIS KUALITAS PELAYANAN RUMAH SAKIT DI PROVINSI BALI - I Nyoman Nurcaya (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2008)
The performance of hospital is influenced by the increasing cost of publichealth service. The increasing cost of public health service are because of the costof human resource which serve the service (input) becoming more expensive andthe patient of the hospital ( output ) has an decreasing ability to pay the publichealth they need. The performance of the hospital could be measured by thequality of the service.The goal of this research is to identify the gap between perceived servicequalities and the medical patient expectation of the service quality. The servicequality gap observes by tangibles factors, reliability, responsiveness, assurance,and empathy.The medical patient who treat in hospital which already applied ISO9001:2000 are the sample of this research. The gap analyses is using theImportance-Performance Analyses program.The measurement of the service quality shown that tangibles variable stilllow in every hospital except Kasih Ibu hospital, the attribute of physicalappearance dan staff appearance are in a good category. Reliability variable arealso low in every hospital except Surya Husadha Hospital, the administrationattributeis in a good category and at BRSU Tabanan Hospital the carenessattribute is also in a good category. Responsiveness variable also shown lowcategory in everi hospital. ssurance varibael shown a low category except SuryaHusadha Hospital, the staff hospitality is in a good category. Emphaty variablealso in a low category except in Surya Husadha, according to service timeattribute is in a good category.